HOUSING AND TRANSPORT EXPENDITURE: AN ASSESSMENT OF LOCATION HOUSING AFFORDABILITY - Hassan, M. Azren; Hamdan, Hazlina; Abdullah, Jamalunlaili; Abdullah, Yusfida Ayu (PLANNING MALAYSIA, 2018)
In every country, the ability to own a house is vital for the housing market. During the past five years, housing prices in the urban area in Malaysia are becoming severely unaffordable. Housing affordability ensures that housing provided is affordable for every income groups, especially the low and middle income group. The measurement of housing affordability uses household income and housing cost but disregards transportation expenditure which is a substantial amount of household expenditure. Location of housing influences transportation expenditure. The research determines the Location Housing Affordability for the low and middle income group in an urban area. This study quantitatively examines Putra Height as one of the mature residential neighbourhoods in Selangor as well as due to the availability of public transit in the area. Housing affordability and transportation affordability create an integrated Location Housing Affordability Index. Data analysis utilizes the measurement of Location Housing Affordability Index. The findings showed that Location Housing Affordability Index recognizes location as influential factor to housing affordability of 179 respondents from low and middle income group. The findings also suggested that the houses in the urban area were seriously unaffordable for the low and middle income groups. The contribution of the research is the emphasis on location as a part of housing affordability measurement.